2010
DOI: 10.3390/molecules15118111
|View full text |Cite
|
Sign up to set email alerts
|

Acute Oral Toxicity and Brine Shrimp Lethality of Elaeis guineensis Jacq., (Oil Palm Leaf) Methanol Extract

Abstract: Elaeis guineensis (Arecaceae) is widely used in West African traditional medicine for treating various ailments. An evaluation on the toxicity of extracts of this plant is crucial to support the therapeutic claims. The acute oral toxicity and brine shrimp lethality of a methanolic extract of this plant was tested. Oral administration of crude extract at the highest dose of 5,000 mg/kg resulted in no mortalities or evidence of adverse effects, implying that E. guineensis is nontoxic. Normal behavioral pattern, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
70
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(81 citation statements)
references
References 12 publications
3
70
0
3
Order By: Relevance
“…Several studies have been conducted to confirm the nontoxicity of different parts of E.guineensis at normal doses (Rajoo et al, 2010;Syahmi et al, 2010). Syahmi et al (2010) evaluated the acute oral toxicity of methanol extract of the leaves using a dose of 5g and found no toxicity.…”
Section: Toxicitymentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have been conducted to confirm the nontoxicity of different parts of E.guineensis at normal doses (Rajoo et al, 2010;Syahmi et al, 2010). Syahmi et al (2010) evaluated the acute oral toxicity of methanol extract of the leaves using a dose of 5g and found no toxicity.…”
Section: Toxicitymentioning
confidence: 99%
“…Syahmi et al (2010) evaluated the acute oral toxicity of methanol extract of the leaves using a dose of 5g and found no toxicity. They also use the brine shrimp bioassay and also reported no toxicity.…”
Section: Toxicitymentioning
confidence: 99%
“…Percentage mortalities were corrected for the natural mortality observed in the negative controls using Abbott's formula, p=(p i -C)/ (1-C), where p i denotes the observed mortality rate and C means the natural mortality. Extracts giving LC 50 values greater than 1.0 mg/mL were considered to be nontoxic [10] .…”
Section: Calculations and Statisticsmentioning
confidence: 99%
“…The last bottle was filled with sea salt water and DMSO only, serving as a drug-free control or negative control. A suspension of larvae (0.1 mL) containing about [10][11][12][13][14][15] larvae was added into each bottle and incubated for 24 h. The bottles were then examined, and the number of dead larvae in each bottle was counted after 24 h. The total number of shrimp in each bottle was counted and recorded. The mean percentage mortality was plotted against the logarithm of concentrations, and the concentration that could kill 50% of the larvae (LC 50 ) was determined from the graph.…”
Section: Brine Shrimp Assaymentioning
confidence: 99%
“…However, recent scientific findings have shown that many plants used as food or in traditional medicine are potentially toxic, mutagenic and carcinogenic (Ajaiyeoba et al, 2006). Toxicity is an expression of being poisonous, indicating the state of adverse effects caused by the interaction between toxicants and cells (Syahmi et al, 2010). Despite the advances in the understanding of the medicinal properties of many herbs and the increased acceptance and utilization of medicinal plants worldwide, the consumer today is confronted with the lack of information or with misinformation concerning the safety of these herbs that rivals the heyday of the patent medicine era (Teshome et al, 2010).…”
Section: Introductionmentioning
confidence: 99%